High-Resolution Quantitative Phase Imaging of Plasmonic Metasurfaces with Sensitivity down to a Single Nanoantenna - Bouchal, Petr; Dvořák, Petr; Babocký, Jiří; Bouchal, Zdeněk; Ligmajer, Filip; Hrtoň, Martin; Křápek, Vlastimil; Faßbender, Alexander; Linden, Stefan; Chmelík, Radim; Šikola, Tomáš (Nano letters, 2019)
Optical metasurfaces have emerged as a new generation of building blocks for multifunctional optics. Design and realization of metasurface elements place ever-increasing demands on accurate assessment of phase alterations introduced by complex nanoantenna arrays, a process referred to as quantitative phase imaging. Despite considerable effort, the widefield (nonscanning) phase imaging that would approach resolution limits of optical microscopy and indicate the response of a single nanoantenna still remains a challenge. Here, we report on a new strategy in incoherent holographic imaging of metasurfaces, in which unprecedented spatial resolution and light sensitivity are achieved by taking full advantage of the polarization selective control of light through the geometric (Pancharatnam-Berry) phase. The measurement is carried out in an inherently stable common-path setup composed of a standard optical microscope and an add-on imaging module. Phase information is acquired from the mutual coherence function attainable in records created in broadband spatially incoherent light by the self-interference of scattered and leakage light coming from the metasurface. In calibration measurements, the phase was mapped with the precision and spatial background noise better than 0.01 and 0.05 rad, respectively. The imaging excels at the high spatial resolution that was demonstrated experimentally by the precise amplitude and phase restoration of vortex metalenses and a metasurface grating with 833 lines/mm. Thanks to superior light sensitivity of the method, we demonstrated for the first time to our knowledge the widefield measurement of the phase altered by a single nanoantenna while maintaining the precision well below 0.15 rad.
Keywords: Pancharatnam−Berry phase; vortex metalens; plasmonic nanoantennas; holographic microscopy; quantitative phase imaging; Plasmonic metasurfaces